2018
DOI: 10.1111/ijd.13875
|View full text |Cite
|
Sign up to set email alerts
|

Influences for gender disparity in dermatology in North America

Abstract: Gender disparity exists in academic dermatology, and the current academics fail to account for the enormous social challenges that women face, which may put them at a disadvantage to career advancement. Among other factors, better representation of female leadership may encourage and inspire women joining academic faculties in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 23 publications
6
51
1
Order By: Relevance
“…There was a significant under-representation of women as faculty in major scientific meetings and in leadership roles of major ICM organisations. These findings are in accord with published data from other specialties of medicine [ 7 – 10 , 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was a significant under-representation of women as faculty in major scientific meetings and in leadership roles of major ICM organisations. These findings are in accord with published data from other specialties of medicine [ 7 – 10 , 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite increasing women graduates, persistent gender gaps exist in the physician workforce, and in particular in some specialties [ 7 – 10 ] and in positions of leadership in all specialties [ 11 ]. Female medical graduates report that they specifically do not choose certain specialties such as critical care medicine (CCM) as their first choice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies found that women were a minority in the academic practice, were at the lower rungs of academic ranks, were disproportionally represented in leadership positions, had lower research productivity and lower H-index scores when compared to men. Similar results were also found in psychiatry and dermatology [4,5]. This suggests that not only is the number of women in a specialty the marker for equality and equity but also their ability to progress academically.…”
Section: Introductionsupporting
confidence: 72%
“…Our methodology has been validated in several recent publications. [1][2][3][4][5]9] We obtained a list of orthopedic programs to gather the academic faculty members of each orthopedic department. The Canadian Resident Matching Service (CaRMS) website enlists a total of 17 university hospitals that offer orthopedic training programs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation